Distinction Between Precapillary and Postcapillary Pulmonary Hypertension by the Atrial Volume Ratio on Transthoracic Echocardiography. (29th September 2017) - Saito, Naka; Kato, Shingo; Saito, Noritaka; Nakachi, Tatsuya; Fukui, Kazuki; Kosuge, Masami; Kimura, Kazuo
Abstract : Objectives: The differential diagnosis between precapillary and postcapillary pulmonary hypertension (PH) is important for deciding on the appropriate therapeutic strategy. The aim of this study was to assess whether the atrial volume ratio can differentiate precapillary and post‐capillary PH. Methods: Seventy‐seven patients with PH who underwent transthoracic echocardiography (TTE) and right heart catheterization were retrospectively studied. Pulmonary hypertension was defined as a mean pulmonary arterial pressure of 25 mm Hg or higher by right heart catheterization. Patients with a pulmonary capillary wedge pressure higher than 15 mm Hg were classified as having postcapillary PH, and patients with a pulmonary capillary wedge pressure of 15 mm Hg or lower were classified as having precapillary PH. The atrial volume ratio derived from TTE was defined as right atrial volume divided by left atrial volume. Results: Forty‐four (57%) of 77 patients had precapillary PH by the right heart catheterization classification. The atrial volume ratio was significantly higher in precapillary PH than in postcapillary PH (1.03 ± 0.69 versus 0.50 ± 0.19; P  < .001). The area under the receiver operating characteristic curve of the atrial volume ratio for detecting postcapillary PH was 0.84 (95% confidence interval: 0.75–0.93). Adding the atrial volume ratio to the left ventricular ejection fraction yielded a high area under the curve of 0.90 (95% confidence interval, 0.83–0.96) for distinguishing precapillary and postcapillary PH. Conclusions: The atrial volume ratio assessed by TTE might be useful for differential diagnosis between precapillary and postcapillary PH.